HINDRANCES TOWARDS DISCLOSING THE HIV POSITIVE STATUS AND ITS EFFECTS ON TREATMENT: A CASE STUDY OF RAWALPINDI CITY - Ahmed, Zubair; Sultan, Haris (European Scientific Journal, ESJ, 2015)
This anthropological research investigated the stigmatization of HIV & AIDS and the discrimination in disclosing HIV positive status to family, peers, relatives and coworkers. However, the narratives and in-depth interviews related to its impact on the treatment, from the point of view of people living with HIV&AIDS, and health care workers were also examined and analyzed. In Rawalpindi, not much has been done to explore the effects of stigmatization and discrimination at the ground levels i.e. personal, family, relatives, friends, acquaintances, work place and care facilities. This study includes all these levels at which HIV positive can face stigmatization and discrimination and its impact on the medical treatment. Informal discussion, participant observation, in-depth interviews, case studies and focus group discussion were conducted with a sample of people living with HIV&AIDS in Rawalpindi and health care providers. Findings indicated that due to the fear of rejection from family, peer, relatives, workplace, and society, individuals with HIV-AIDS do not disclose their status with any of their affiliates. Blaming and rejection are the two key aspects which are unbearable for the patients, furthermore, the factor of shaming also plays an important role in resistance of HIV positive status disclosure. Findings suggest that individuals with HIV&AIDS faced the threat of stigmatization and discrimination by family, friends and other institutions of the society. Society does not accept HIV&AIDS patients with ease. That is the reason most of the individuals remained silent about their HIV positive status. This condition has also an effect on the treatment of HIV positive patients. Therefore, many such individuals do not expose their status because of stigma status attached with this never-ending disease.Ultimately, the hiding part causes great harm to the patient as the treatment is hindered by this. When status is not known by the people around, it becomes quite difficult to get proper care and required treatment. This article explained in depth the fears of patients when it comes to disclose their status with family members.